Computational Intelligence for Traffic and Mobility - Wang, Wuhong; Wets, Geert; SpringerLink (Online service) (Paris : Atlantis Press : Imprint: Atlantis Press, 2013)
This book presents the new development of computation intelligence for traffic, transportation and mobility, the main contents include traffic safety, mobility analysis, intelligent transportation system, smart vehicle, transportation behavior, driver modeling and assistance, transportation risk analysis and reliability system analysis, vehicle operation and active safety, urban traffic management and planning.
Sequential Advanced Guide Signing For Work Zone Related Rerouting On Highways -- The Relationship between Driver Fatigue and Monotonous Road Environment -- Driving Situation Awareness in Transport Operations -- Container Drayage Operations at Intermodal Terminals -- Application of Genetic Algorithm to Optimize Transit Schedule under Time-Dependent Demand -- Validation of an Activity-Based Traffic Demand Model for Flanders -- Driver Behaviour in Conflict with Redcrossing Pedestrians -- Cellular Automaton Model and Simulation of Traffic and Mobility Operations -- A Data Imputation Method with Support Vector Machines -- VLSN Search Method Based Hubs Location and Service Frequency Determination -- Quantitative Risk Assessment for Traffic and Mobility Safety -- Investigating the Progress towards Sustainable Road Transport in Europe -- Modeling of Traffic Behavior in Traffic Safety -- Applications of Multi-Source Traffic Data on Mobility Analysis for Urban Road Network -- Practical Methods in Traffic Demand Forecasting Model.
Keywords: Computer science; Information systems; Computer simulation; Computer Science; Information Systems and Communication Service; Simulation and Modeling